Growth and Phytochemistry of Cymbopogon citratus Stapf Inoculated with Plant Growth-Promoting Bacteria under Different Lead Levels - Sete da Cruz, Rayane Monique [UNESP]; Ferreira, Henrique; Jaski, Jonas Marcelo; Vieira, Marcelo Coelho Esperança; Pinc, Mariana Moraes; de Souza, Silvia Graciele Hülse; Alberton, Odair (MDPI, 2024)
This study aimed to investigate the phytochemistry of lemongrass (Cymbopogon citratus) inoculated with Azospirillum brasilense and grown in lead (Pb)-contaminated soil to assess its responses to inoculation under different Pb levels. The experimental design was completely randomized in a 2 × 5 factorial scheme: two levels of A. brasilense (absence or presence) and five Pb levels. After four months of treatment, the following were analyzed: total and reducing sugars, total phenolic content, flavonoids, antioxidant activity, antioxidant enzymes, proline, and essential oil (EO) content and composition. Soil Pb levels and A. brasilense inoculation affected phytochemicals in lemongrass plants. Azospirillum inoculation reduced total sugars in the roots at all soil Pb levels, while increasing Pb levels favored a rise in sugar contents. There was an increase in flavonoid content in treatments associated with Pb and inoculated with A. brasilense. Antioxidant capacity was lower at lower Pb levels, regardless of bacterial inoculation. Enzymatic response was mainly affected by Pb concentrations between 50 and 100 mg kg−1 soil. EO content was influenced by soil Pb levels, with higher EO production at 500 mg Pb kg−1 soil and without A. brasilense inoculation. Overall, lemongrass cultivation in Pb-contaminated areas can be an alternative to phytoremediation and EO production for the industry.
Keywords: essential oil; lemongrass; PGPB; phytoremediation; rhizosphere; soil rehabilitation